ISOLATION AND IDENTIFICATION OF SECONDARY METABOLIT COMPOUNDS IN ETIL ASETIC FRACTIONS ON MINDI LEAF - Nurul Lutfia; Sri Atun (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2018)
This study was aimed at isolating and identifying secondary metabolites contained in the ethyl acetate fraction of parasitic leaves (Dendrophthoe falcata (L.f)) Ettingsh which attaches to the stem of Mindi plants (Melia azedarach). The subjects in this study were leaves of parasitic plants on Mindi plants. While the objects in this study were secondary metabolites from the ethyl acetate fraction of the leaves of parasite plants attached to the mindi plant. The research method was carried out by extracting macerated leaves of D. falcata with ethanol solvents. The ethanol extract obtained was partitioned using n-hexane, chloroform, and ethyl acetate. Ethyl acetate fraction was separated by gravity column chromatography (CCG). The relatively non-polar fraction that has shown a single stain is tested for purity using 3 different types of solvents and identified using UV-Vis, IR, and GC-MS. The results showed that the compounds that could be isolated and identified from the relatively non-polar ethyl acetate fraction of D. falcata leaves were stigmast-5-en-3β-ol with an abundance of 6.49%, having a molecular weight of m / z 414 with base peak 55. Compounds sterols are compounds commonly found in parasitic plantsISOLASI DAN IDENTIFIKASI SENYAWA METABOLIT SEKUNDER PADA FRAKSI ETIL ASETAT DAUN MINDIPenelitian ini bertujuan untuk mengisolasi dan mengidentifikasi senyawa metabolit sekunder yang terdapat dalam fraksi etil asetat daun benalu (Dendrophthoe falcata (L.f)) Ettingsh yang menempel pada batang tumbuhan Mindi (Melia azedarach). Subjek dalam penelitian ini adalah daun tumbuhan benalu pada tanaman mindi. Sedangkan objek dalam penelitian ini adalah senyawa metabolit sekunder dari fraksi etil asetat daun tumbuhan benalu yang menempel pada tanaman mindi. Metode penelitian dilakukan dengan ekstraksi maserasi daun D. falcata dengan pelarut etanol. Ekstrak etanol yang diperoleh dipartisi menggunakan n-heksana, kloroform, dan etil asetat. Fraksi etil asetat dipisahkan secara kromatografi kolom gravitasi (KKG). Fraksi relatif non polar yang sudah menunjukkan noda tunggal diuji kemurniannya menggunakan 3 jenis pelarut yang berbeda dan diidentifikasi menggunakan UV-Vis, IR, dan GC-MS. Hasil penelitian menunjukkan senyawa yang dapat diisolasi dan diidentifikasi dari fraksi etil asetat relatif nonpolar daun D. falcata adalah stigmast-5-en-3β-ol dengan kelimpahan 6,49 %, memiliki berat molekul m/z 414 dengan base peak 55. Senyawa sterol merupakan senyawa yag lazim ditemukan dalam tumbuhan benalu.